TEKNOLOGI PEMANEN KABUT (FOG HARVESTING) SEBAGAI SOLUSI MENGATASI MASALAH KEKERINGAN PADA DATARAN TINGGI - Taufani, Aditya Riski; Utomo, Puji; Maulana, Taufiq Ilham; Musofa, Musofa (Program Kreativitas Mahasiswa - Penelitian, 2013)
Drought occur in Ngoho Plateu, Semarang and always happened in dry season. However, the plateu has a big potential of fog, which always occur in wet and dry season. This research purposes to determine the potential of fog Â harvesting, 4 models of standard fog collectors (SFC) were installed in two locations. Each location were installed 2 models with azimuth of 90o and 180o. Data collected for 4 months, on condition where foggy day only. Equipment that harvested largest amount of fog water was model 4 which were mounted on highest land of plateu azimuth of 90o. Model 4 was capable to harvest water 8 liter/m2 in fog duration of 8 hours.Â Keywords : water, fog, standard fog collector